Relationship of Family Support to Compliance in Taking Medication for ODGJ Post-Treatment (HEALTH CARE: JURNAL KESEHATAN, 2025)
One important aspect for the recovery of ODGJ patients is patient compliance in taking medication. Compliance in taking medication requires family support, because patients are not yet able to organize and know the schedule and types of drugs to be taken. The purpose of this study was to determine the relationship between family support and compliance in taking medication in post-treatment mental disorder patients. The study was conducted in the Tatakarya Health Center working area with a quantitative analytical design using a cross-sectional approach. The sample of this study was all post-treatment patients from a mental hospital totaling 50 respondents. The research instrument was in the form of statements about family support and compliance in taking medication with a Cronbach alpha value of 0.637. The independent variable is family support and the dependent variable is compliance in taking medication. Bivariate analysis using Chi-Square. The results of the study showed that 62% had high family support and 58% had high compliance in taking medication. There is a significant relationship between family support and compliance in taking medication in post-treatment mental disorder clients, p = 0.000. In further research, a scale of compliance in taking medication can be used.